Учёт мотивационных факторов при создании учебных пособий для иностранных студентов - Гейченко, Е. И.; Гейченко, Катерина Іванівна; Geychenko, K. I. (К. : КІМ, 2016)
Among many different and difficult questions that are connected with the language preparation of foreign citizens, who study in universities of Ukraine, a special place occupies an issue of didactical organization of the process. It must be organized so that the students were interested in the subject, and in the foreign language in particular. To get much higher results in learning a foreign language among the foreign students it is necessary to arise their conscious and active interest. In order to get these results it is necessary to promote complex motivation during the language learning and consciously to use factors that arise motivation. According to this, textbooks play a great role in the educational process. The aim of this article is to pay attention of teachers-linguists and methodists, who do the language preparation of the foreign students in non-philological universities, to some psychological aspects and motivation factors, that must be taken into consideration during the preparation of educational materials. It is a well-known fact, that the contents of education is a positive motivational factor, if it corresponds with the needs and interests of the foreign students. So, the topic and its contents must contain such facts, that arise the students’ interest and correspond with their communicational intentions. In our opinion, while creating the educational materials, the authors must clearly understand, how it is possible to join the foreign student to the communicational act, that he will actively participate in solving communicational tasks, what type of exercises are the most suitable for the development of communication, orally or in writing; how to provide reasonable combination of exercises for the development of communicational skills in the communicational direction of education; how to provide reasonable combination of language and speech exercises for obtaining the communicational aim.
Урахування мотиваційних факторів при розробці навчальних посібників для іноземних студентів
Accounting motivational factors when creating textbooks for foreign students
Keywords: іноземні студенти; мовна підготовка; мотивація; навчальні посібники; educational materials; foreign students; motivation; language preparation